2014
DOI: 10.3109/01443615.2014.969207
|View full text |Cite
|
Sign up to set email alerts
|

Placental and infant metastasis of maternal melanoma: A new case

Abstract: Obstetric Case Reports 417 diagnostic resources, support and a multidisciplinary team trained for clinical emergencies in pregnancy are essential for the successful treatment of such severe cases.Risk factors for amniotic embolism include maternal age below 20 and above 35 years, elderly primigravidity, grand multiparity, black race, previous caesarean section, induction of labour, caesarean delivery, forceps delivery, vacuum delivery, multiple pregnancy, placenta previa, abruptio placenta, pre-eclampsia, ecla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…The planning of the delivery was established according to a number of different parameters, such as disease progression, maternal schedule treatment and foetal risks associated with the maternal treatment, and general maternal conditions (Azim, Pavlidis, et al., ; Azim, Peccatori, et al., ; De Carolis et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…The planning of the delivery was established according to a number of different parameters, such as disease progression, maternal schedule treatment and foetal risks associated with the maternal treatment, and general maternal conditions (Azim, Pavlidis, et al., ; Azim, Peccatori, et al., ; De Carolis et al., , ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2002, a comprehensive review identified 27 cases of placental metastasis over the preceding 40 years [32], with 6 (22%) of these cases also reporting foetal metastatic spread [32]. Based on this study and a few case reports [33,34] it is widely accepted that foetal involvement can be reasonably excluded in the absence of macro-or microscopic placental involvement [35]. Outcomes are generally poor for affected foetuses, with the majority of infants (>80%) dying from disease [32].…”
Section: Placental and Transplacental Metastatic Spreadmentioning
confidence: 94%
“…We selected 8 cases from 10 articles (two articles described the same cases) reporting transplacental transmission of melanoma, which are summarized in Table S5. [280][281][282][283][284][285][286][287][288][289] The mean age at diagnosis was 5.3 months (range: 0.37-10), six were males, most of them presenting multiple localisations of melanoma metastasis at diagnosis. The number of melanoma-related deaths was 5, and three patients underwent spontaneous regression.…”
Section: Transplacental Melanomamentioning
confidence: 99%